Exploring the origin of pain subclassification, with emphasis on low back pain: a scoping review. Issue 2 (1st February 2021) - Jess, Mary-Anne; Hamilton, Sharon; Ryan, Cormac; Wellburn, Shaun; Alexanders, Jenny; Spence, Daniel; Martin, Denis
ABSTRACT: Objective: This scoping review aimed to explore the different working definitions for the duration of acute, subacute, and chronic pain, with emphasis on low back pain, and to establish where these definitions originated and the rationale provided for the time frames used. Introduction: From a global perspective, low back pain is a major social and economic problem. One of the most commonly used methods to stratify and manage low back pain is the traditional duration-based classification (acute, subacute, and chronic). Where these time points lie to differentiate these transitions continues to be debated within the scientific community, which may engender a degree of heterogeneity in study findings. Therefore, applying these findings to clinical practice may be somewhat challenging. This review encapsulates the historical origins of the different duration categories to provide an understanding of how these variations were derived. Inclusion criteria: Studies that included participants with low back pain were the focus of this review. Sources that included children or other specific pain pathologies, such as cancer pain, were excluded. The main concept of interest was that the publication proposed an original definition of the duration of acute, subacute, or chronic low back pain. All study designs were included provided they gave a rationale for the duration that they used. Methods: The following databases were searched: MEDLINE, Embase, CINAHL, and PsycINFO, from the inception of each database until September 18, 2019. This review was limited to studies published in English. Two independent reviewers screened the retrieved articles against the eligibility criteria. Additional studies were searched from the reference lists of studies to find the original source. Some original sources overlapped with general pain duration literature. This led to a deviation from the scoping review protocol, which originally intended to focus on definitions of low back pain duration only. Data extraction was undertaken using a charting table developed specifically for the review objectives. The findings were presented using narrative synthesis. Results: Nineteen records were included in this review, and comprised three book chapters, four review articles, four articles that arose following pain expert group discussions, seven primary research studies, and a spinal guideline. Data were extracted from the included studies and categorized into four themes based on the origin of the classification of the duration. The themes included i) work/employment setting, ii) empirical studies, iii) expert reasoning, and iv) pathophysiological explanation. Conclusions: This scoping review compiled the existing literature on the working definitions of the duration of acute, subacute, and chronic low back pain and found a wide variation. These ranged from seven days, 14 days, and seven weeks for the acute and subacute transition points, and seven weeks to three years for chronic low back pain. The duration definitions specifically referring to the general pain literature focused on three and/or six months for the transition to chronic. Better integration of reasoning between the identified themes could facilitate the establishment of more ideal duration definitions in the future. Although inconclusive, the definition most commonly cited, with most consensus, was three months for the transition to chronic low back pain.